2006
DOI: 10.2116/analsci.22.39
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Arsenic Species in Marine Samples by HPLC-ICP-MS

Abstract: IntroductionAs far we have developed the very high sensitive methods for determining trace and ultratrace elements by combination between flow injection analysis (FIA) with on-line column preconcentrating techniques and inductively coupled plasma mass spectrometry (ICP-MS), such as trace metals (Cr(III), Al, V, Mn, Co, Ni, Cu, Zn, Mo, Cd, Pb and U) in seawater 1-3 and rare earth elements (Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu) in seawater. [4][5][6] Therefore, since an ICP-MS instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 32 publications
6
33
0
1
Order By: Relevance
“…It is known that seafood and marine samples contain various organic arsenic compounds, such as AsBe, AsCho, DMA, and AsSug 15) . Using liquid chromatography coupled to tandem quadrupole mass spectrometry, we found six oxo-arsenosugars in extracts from hijiki seaweed sold in a Japanese market 16) .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that seafood and marine samples contain various organic arsenic compounds, such as AsBe, AsCho, DMA, and AsSug 15) . Using liquid chromatography coupled to tandem quadrupole mass spectrometry, we found six oxo-arsenosugars in extracts from hijiki seaweed sold in a Japanese market 16) .…”
Section: Resultsmentioning
confidence: 99%
“…For the biological monitoring of exposure to iAs, the seafood intake should not interfere with the urinary concentrations of iAs metabolites 2,3 ) . ACGIH and DFG use the total concentration of urinary iAs+MMA+DMA, excluding AsBe, for the biological monitoring of occupational exposure to iAs 2,16) , because AsBe is the main arsenic compound in fish and shellfish 4,18 ) . ACGIH reported that the urinary arsenic concentrations in the general population were approximately 10 μg As/l in European countries and the United States and approximately 50 μg As/l in Japan 2) .…”
Section: Discussionmentioning
confidence: 99%
“…The total concentration of iAs and its metabolites, MMA and DMA, excreted in urine has been used for the biological monitoring of occupational iAs exposure by the American Conference of Governmental Industrial Hygienists (ACGIH) and Deutsche Forschungsgemeinschaft ( DFG ) 2,3 ) . In addition to DMA, methylated arsenics such as arsenobetaine (AsBe), arsenocholine (AsCho), and arsenosugars (AsSugs) are abundant in seafood products 1,4 ) . Although AsBe is only minimally metabolized in mammals 5) , AsCho and AsSug are extensively metabolized to AsBe and DMA 6,7) , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many analytical techniques have been developed for the chemical speciation of elements in environmental samples: typically, sequential leaching methods, [3][4][5][6][7] hyphenated techniques, [8][9][10][11][12] such as GC-ICP-MS (analysis of organometallic elements), X-ray spectroscopic techniques and others. [13][14][15] These methods provide significant information on the chemical forms of elements in the environment.…”
Section: Introductionmentioning
confidence: 99%